2022
DOI: 10.1038/s41398-022-02052-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and risk of neurodegenerative disorders: A Mendelian randomization study

Abstract: Emerging evidence has suggested a close correlation between COVID-19 and neurodegenerative disorders. However, whether there exists a causal association and the effect direction remains unknown. To examine the causative role of COVID-19 in the risk of neurodegenerative disorders, we estimated their genetic correlation, and then conducted a two-sample Mendelian randomization analysis using summary statistics from genome-wide association studies of susceptibility, hospitalization, and severity of COVID-19, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 46 publications
5
52
1
Order By: Relevance
“…One emerging hypothesis following observations of persistent long-term cognitive difficulties and physiological patterns after COVID-19 suggests a potential trigger or accelerator of neurodegenerative process ( Beauchet and Allali, 2022 , McAlpine et al, 2021 ). Indeed, different studies have shown that COVID-19 associates with neurotoxicity, hippocampal degeneration, and increased risk of Alzheimer's disease ( Bayat et al, 2022 , Chiricosta et al, 2021 , Li et al, 2022 ). However, although the hypothesis of an initiation (or acceleration) of neurodegenerative cascades is central after COVID-19 infection, other hypotheses that limbic encephalitis after COVID-19 ( Franke et al, 2023 , Franke et al, 2021 ) would result in persistent cognitive symptoms could potentially be another interesting avenue (Shnayder et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One emerging hypothesis following observations of persistent long-term cognitive difficulties and physiological patterns after COVID-19 suggests a potential trigger or accelerator of neurodegenerative process ( Beauchet and Allali, 2022 , McAlpine et al, 2021 ). Indeed, different studies have shown that COVID-19 associates with neurotoxicity, hippocampal degeneration, and increased risk of Alzheimer's disease ( Bayat et al, 2022 , Chiricosta et al, 2021 , Li et al, 2022 ). However, although the hypothesis of an initiation (or acceleration) of neurodegenerative cascades is central after COVID-19 infection, other hypotheses that limbic encephalitis after COVID-19 ( Franke et al, 2023 , Franke et al, 2021 ) would result in persistent cognitive symptoms could potentially be another interesting avenue (Shnayder et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As the population of patients recovering from COVID-19 grows, it is important to establish an understanding of the multi-organ dysfunction associated with post-COVID-19 complications. Of note, neurological manifestations in COVID-19 patients have been reported, showing a close correlation between COVID-19 and future development of neurodegenerative diseases (Wu et al, 2020b;Taquet et al, 2021;Frontera et al, 2022;Li et al, 2022a). It has also been established that the likelihood of developing COVID-19-associated cognitive impairment and the severity of these deficits is associated with the severity of the SARS-CoV-2 infection and the subsequent increases in specific circulating inflammatory mediators and biomarkers (Becker et al, 2021;Miskowiak et al, 2021;Zeng et al, 2022).…”
Section: Covid-19-associated Cognitive Dysfunction and Neurodegenerat...mentioning
confidence: 92%
“…The direct viral infection of the brain has also been proposed as a cause for these symptoms, as SARS-CoV-2 viral proteins were detected in the brain tissue of patients who died from COVID-19 ( Matschke et al, 2020 ). It has been suggested that increased COVID-19 susceptibility and severity could increase the risk for neurodegenerative disorders ( Li et al, 2022 ). While further investigations are required to clarify a causal link, these collective findings demonstrate the importance of understanding the neurodegenerative sequelae of viral infections.…”
Section: Pathophysiology Of the Lc In Aging And Neurodegenerative Dis...mentioning
confidence: 99%